IJCM_5A: A gender perspective of gender equity and health amongst youth of urban slum area in South Gujarat - Gusain Teesta; Verma Mamtarani; Gamit Chintan (Wolters Kluwer Medknow Publications, 2024)
Background: The socially constructed characteristics, qualities and actions of men, women, girls, and boys are referred to as gender. Being a core social determinant, it directly affects attitude and health related behaviour. The variance in exposure to material, psychological, behavioural, and biological aspects is how gender impacts health outcomes. Objectives: To document the knowledge regarding gender equity, violence, sexuality, masculinity and reproductive health. To determine gender wise differences in access to healthcare and perception of one's own health. Methodology: A cross-sectional study was carried out in the urban health centre field practise area in Surat, Gujarat among 260 youth participants aged 18-24 years. After obtaining ethical approval, participants were selected via convenient sampling technique, written informed consent was obtained. Data was collected through face-to-face interviews maintaining privacy using a pre-tested semi structured questionnaire for a duration of 8 months. Data was entered in excel and analysed using JAMOVI software. Themes were generated for qualitative responses. Results: 147 (56.5%) participants were males. The mean age of the participants was 20.55+2.14. Females had statistically significant higher mean gender equity score (30.90+4.68) than males (26.60+3.27). Significant association was seen for education (p= 0.005) and sibling type (p= 0.005) with gender equity. Negligible positive and significant correlation (r= 0.12) between gender equity scores and total family income. Multiple roles and responsibilities (26.7%) were the major factor identified for perception of health. Conclusion: Results highlight the importance of education and employment in developing high gender equitable attitudes The barriers for accessing healthcare services were varied like autonomy to take decision, monetary problems distance to healthcare services etc. Multiple roles, treatment seeking behaviour and reproductive health were major areas which influenced youth's perception of their health.